FAKTOR PENYEBAB KERUSAKAN SISTEM MESIN PADA BUS APTB PPD - Chairani, Laela; Usman, Yulita Veranda; Hidayah, Nur Yulianti (Universitas Muhammadiyah Surakarta, 2015)
Comfort and safety of public transportation, particularly APTB PPD buses, becomes high expectations for its customers. Those expectations must be supported by the application of a good engine maintenance system. By using the method of Reliability Centered Maintenance may be determined appropriate actions to mitigate damage. From the analysis known the failures of the APTB PPD bus are malfunctions of the fuel engine, power transfer systems, difficulty to move the gear lever, and lubricating system for the rough engine noise. The cause of engine malfunction is dirty diesel filter, vehicle acceleration malfunction is due to the clutch plate wear out. Difficulty to move the gear lever indicates that the clutch slips. Rough engine noise caused by the flow of oil to the engine stalled as the result of dirty oil filter. The results of the logic tree analysis show that for each failure requires scheduling of time directed task.